Enhancement in resistivity resolution based on the data sets amalgamation technique at Bukit Bunuh, Perak, Malaysia - Bery, Andy Anderson; Saad, Rosli; Hidayah, I.N.E; Azwin, I.N.; Saidin, Mohd Mokhtar (IOP Publishing, 2015)
In this paper, we have carried out a study with the main objective to enhance the resolution of the electrical resistivity inversion model by introducing the data sets amalgamation technique to be used in the data processing stage. Based on the model resistivity with topography results, the data sets amalgamation technique for pole-dipole and wenner-schlumberger arrays are successful in identifying the boundary or interface of the overburden and weathered granite. Although the electrical resistivity method is well known, the proper selection of an array and appropriate inversion parameters setting such as damping factors are important in order to achieve the study objective and to image the target at the Earth’s subsurface characterizations.